6y-6y-12y=please help me


The answer is -12y Explanation: Since all the numbers have a common variable you can just add all of them together. 6y - 6y = 0 0 - 12y = -12y

0 0

Hello. The answer is  -12y Combine Like Terms:=6y +−6y +−12y =(6y +−6y +−12y ) =−12y Have a nice day

0 0
Only authorized users can leave an answer!
Can't find the answer?

If you are not satisfied with the answer or you can’t find one, then try to use the search above or find similar answers below.

Find similar answers

More questions

Mathematics, added 2020-04-02 05:31:37

Both questions please ...